2019
DOI: 10.1111/jpn.13061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron glycine chelate on laying performance, antioxidant activities, serum biochemical indices, iron concentrations and transferrin mRNA expression in laying hens

Abstract: This study was conducted to evaluate the effects of iron glycine chelate (Fe‐Gly) on laying performance, antioxidant enzyme activities, serum biochemical indices and iron concentrations in laying hens. A total of 810 laying hens (Hy‐Line Variety White, 26 weeks old) were randomly assigned to six groups with five replicates of 27 layers. Hens in the control group received diet supplemented with 60 mg Fe/kg as FeSO4, while hens in other five groups received the diet supplemented with 0, 20, 40, 60 and 80 mg Fe/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…ALB content accounts for the largest protein fraction (40-60%), and it is synthesized in the liver [46]. Both TP and ALB contents in the blood are considered markers of liver function that reflect protein synthesis [47]. TP and ALB levels decrease in rats under ferrous sulfate-induced oxidative stress conditions [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…ALB content accounts for the largest protein fraction (40-60%), and it is synthesized in the liver [46]. Both TP and ALB contents in the blood are considered markers of liver function that reflect protein synthesis [47]. TP and ALB levels decrease in rats under ferrous sulfate-induced oxidative stress conditions [45,48].…”
Section: Discussionmentioning
confidence: 99%
“…Some early studies found that the bioavailability of Fe-Gly was at least 2 times more than FeSO4 [14,21,22]. Supplementing Fe-Gly in laying hens increased LR and egg weight compared with FeSO4, while ADFI and FCR showed no differences [23]. Adding Fe-Gly in the basal diet enhanced performance of hens and decreased the abnormal egg rate in contrast to inorganic ferrous [6].…”
Section: Laying Performancementioning
confidence: 99%
“…Several studies shown that supplementing organic source of iron could improve antioxidant capacity of the body. The activities of T-SOD and Cu/Zn-SOD were raised along with the growth of additive dosage of Fe-Gly [23]. The Fe-Gly supplementation effectively increased the activities of SOD and decreased the content of MDA in serum of layers at 9 wk and 12 wk of the experiment [6].…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…According to research, amino-chelated or proteinated sources of iron are preferable to FeSO4 as a form of iron supplementation [31,32]. Then again, other studies discovered that the inorganic and organic sources (amino acid complexes) were equivalent in terms of mineral retention and eggshell quality [33]. When Fe-Lys-Glu was given to hens at a dosage of 45 mg/kg, the yolk Fe content was higher (p <0.05) than when FeSO4 was added at the same dosage [34].…”
Section: Manganese (Mn)mentioning
confidence: 99%